1983
DOI: 10.1111/j.1432-1033.1983.tb07658.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of N-acetyl-L-glutamate to rat liver carbamoyl phosphate synthetase (ammonia)

Abstract: The binding of N-acetyl-L-glutamate, the physiological allosteric activator, to rat liver carbamoyl-phosphate synthetase (ammonia) was studied by techniques of rate of dialysis and of ultracentrifugation in the Airfuge. There is one binding site for acetylglutamate per enzyme monomer ( M , 165 000). K ', Mg2 + (free) and ATP were required to demonstrate binding. The concentrations of ATP required indicate that binding of ATPA (the ATP molecule that yields Pi) is needed. HCO; was not essential, but it enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 24 publications
6
44
0
Order By: Relevance
“…They also observed that both Mg2+ and ATP are required for binding of N-acetylglutamate to the enzyme. Their studies are described in the accompanying paper [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed that both Mg2+ and ATP are required for binding of N-acetylglutamate to the enzyme. Their studies are described in the accompanying paper [35].…”
Section: Discussionmentioning
confidence: 99%
“…Rubio and coworkers [35] also recently established the conditions for binding of N-['4C]acetylglutamate to carbamoyl-phosphate synthetase, using the purified enzyme. They also observed that both Mg2+ and ATP are required for binding of N-acetylglutamate to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated, using rate of dialysis and ultracentrifugation [7], that the enzyme binds one molecule of [14C]acetylglutamate with high affinity (Kd % 0.6 -1 pM) when K + and Mgz+ (which are essential ionic activators of the enzyme) and a mixture of either ADP and carbamoyl phosphate or ATP and HCO; are present. HCO; appears not to be essential, although it increases the affinity substantially.…”
Section: Mg2+>kt 2 Adpmentioning
confidence: 99%
“…We have previously demonstrated, using rate of dialysis and ultracentrifugation [7], that the enzyme binds one molecule of [14C]acetylglutamate with high affinity (Kd % 0.6 -1 pM) when K + and Mgz+ (which are essential ionic activators of…”
Section: Mg2+>kt 2 Adpmentioning
confidence: 99%
“…However, the activator for rat carbamoylphosphate synthetase, acetylglutamate, has been shown to remain in rapid exchange with the solution despite a slow activation process taking many minutes that is associated with a very marked increase in affinity of the enzyme for acetylglutamate [31,32].…”
Section: Discussionmentioning
confidence: 99%